Kilas Balik Sang Pembaharu - Cucum Novianti (Misykah : Jurnal Pemikiran dan Studi Islam, 2020)
Education is generally not given to women, so that women remain in ignorance and suffering. Abduh is of the view that the disease stems, among other things, from the ignorance of Muslims on the true teachings of religion, because they learn in an inappropriate way. According to Abduh, the disease can be treated by educating them with the right teaching system. The education system that existed in his time was the background for Muhammad Abduh's educational thinking. Previously, the reform of Egyptian education was initiated by Muhammad Ali. He only emphasized the development of the intellectual aspect and left two types of education to the next period. The first model is modern schools, while the second model is religious schools. Each school stands alone, without having a relationship with each other. Religious schools are not given lessons in modern sciences from the West, so that intellectual development is reduced. Meanwhile, schools run by the government are only given Western knowledge, without providing religious knowledge. Abstrak Pendidikan pada umumnya tidak diberikan kepada kaum wanita, sehingga wanita tetap tinggal dalam kebodohan dan penderitaan. Abduh berpandangan bahwa penyakit tersebut antara lain berpangkal dari ketidaktahuan umat Islam pada ajaran agama yang sebenarnya, karena mereka mempelajari dengan cara yang tidak tepat. Menurut Abduh, penyakit tersebut dapat diobati dengan cara mendidik mereka dengan sistim pengajaran yang tepat. Sistim pendidikan yang ada pada masanya yang selanjutnya melatarbelakangi pemikiran pendidikan Muhammad Abduh. Sebelumnya, pembaruan pendidikan Mesir diawali oleh Muhammad Ali. Dia hanya menekankan pada perkembangan aspek intelektual dan mewariskan dua tipe pendidikan pada masa berikutnya. Model pertama ialah sekolah-sekolah moderen, sedang model kedua adalah sekolah agama. Masing-masing sekolah berdiri sendiri, tanpa mempunyai hubungan satu sama lain. Pada sekolah agama tidak diberikan pelajaran ilmu-ilmu moderen yang berasal dari Barat, sehingga perkembangan intelektual berkurang. Sedangkan sekolah-sekolah yang diselenggarakan oleh pemerintah, hanya diberikan ilmu pengetahuan Barat, tanpa memberikan ilmu agama